Implementasi Program Kampung Iklim Di Kelurahan Kampung Bugis Kota Tanjungpinang - Edward Mandala; Rendra Setyadiharja; Suhardi Mukhlis; Nurbaiti Usman Siam; Zangki Firdaus (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The Climate Village Program aims to create villages or neighborhoods that are sustainable in terms of the environment and economy, while also reducing the impacts of climate change by increasing community participation in tangible actions to address climate challenges. This study aims to evaluate the implementation of the Climate Village Program (ProKlim) in Kampung Bugis Village. Its implementation is based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.84/MENLHK-SETJEN/KUM.1/11/2016 concerning the Climate Village Program. This study applies the program implementation theory by Van Meter and Van Horn, which examines various factors influencing the success of a program. The population in this study consists of the Climate Village Implementing Group in Kampung Bugis Village, with a total of 74 members. The research sample was selected using purposive sampling, involving six individuals from two different groups to obtain representative data. This study employs aqualitative method. Thestudy concludes that the implementation of the Climate Village Program in Kampung Bugis Village aligns with its intended objectives, although some aspects still need improvement to achieve more optimal results. The researcher suggests that the government enhance support and facilities for the Climate Village Implementing Group and encourage active community participation. Continuous training and education should be improved to strengthen the group's capacity in addressing climate change challenges. Additionally, a sustainable evaluation and monitoring mechanism is needed to periodically assess the program's performance and ensure it runs as planned and achieves its desired goals.